Thai ‘Healthy Schools’ teacher professional competency needs development analyses - Chatkaew Kanawapee; King Mongkut; Sirirat Petsangsri; Paitoon Pimdee; N Achwarin; M Auld; M Allen; C Hampton; J Montes; C Sherry; A Mickalide; R Logan; et al. (İlköğretim Online, 2021)
In a COVID-19 pandemic world, health education and by extension student and community health literacy (HL) have become critical aspects of a school's student and community health education. As such, this study set out in 2020 to identify and investigate Thai 'Healthy School' (HS) teacher competency needs levels, both actual and desired. Using multiple-stage random sampling techniques, 341 teachers were selected for the study from three regions across Thailand. Data were analyzed using IBM's SPSS version 21 for the descriptive statistics, including the mean ( ) and standard deviation (S.D.). Excel software was used for the modified priority needs index (PNIModified) analysis. From the teacher responses from the 63 item survey, it was determined that the 'Healthy School' education teachers perceived their competency needs to be at a 'high' level. Furthermore, the results revealed that HS teachers perceived their highest competency needs to be their curriculum management and learning management (CMLM) and analysis, synthesis, and research for learner development (ASR). However, HS teachers regarded their community relationship building and partnerships for basic learning (CRBPBL) as the least important. Finally, as the COVID-10 pandemic continues to ravage the world, Thailand's HS education teacher competencies play an even more critical role in Thailand's ability to recuperate and prosper.
Keywords: Educational Assessment and Improvement; Teacher Education and Leadership Studies; Education and Teacher Training